Pembelajaran Pendidikan Agama Islam di Masa Pandemi Covid-19 - Putra, Mahendra (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2022)
Pandemic Covid-19 impact systemic and significant in all aspects of life, one of them on the education system. Changes in the education system especially in the learning required to innovate so that learners did not trouble to receive the material, especially in Elementary School (SD) and Kindergarten (TK), given the learning which is usually carried out for conventional prosecuted and forced into distance learning or done online.This study uses the method of critical analysis that describes the idea of a particular object. As for the object of study is the thought or idea of man are revealed on the primary data and secondary data using data collection techniques from the research literature (library research) by way of studying the manuscripts, books, records, journals, articles, and so on, which discusses the learning of Islamic education and innovation education of Islam that occurred in the era of Pandemic Covid-19.The results of the study explained that the utilization or innovation learning of Islamic Religious Education should be carried out, especially in some of the learning methods. The Internet as a learning medium can be an alternative method of learning Islamic religious education, this can be in the form of e-learning, or applications that facilitate the delivery of learning material, so that the learning process more interesting and not boring.Keyword: Learning; Islamic Education; The Pandemic Covid-19. Abstrak Pandemi Covid-19 memberikan dampak sistemik dan signifikan diseluruh aspek kehidupan, salah satunya pada sistem pendidikan. Perubahan sistem pendidikan terutama pada pembelajaran dituntut untuk berinovasi supaya peserta didik tidak kesulitan untuk menerima materi, terlebih di jenjang Sekolah Dasar (SD) dan Taman Kanak-kanak (TK), mengingat pembelajaran yang biasanya dilakukan secara konvensional dituntut dan dipaksa menjadi pembelajaran jarak jauh atau dilakukan secara daring.Penelitian ini menggunakan metode analisis kritis yang menggambarkan gagasan mengenai objek tertentu. Adapun objek kajiannya adalah pemikiran atau gagasan manusia yang terungkap pada data primer dan data sekunder yang menggunakan teknik pengumpulan data dari penelitian kepustakaan (library research) dengan cara menelaah naskah, buku, catatan-catatan, jurnal, artikel, dan sebagainya yang membahas tentang pembelajaran pendidikan Islam maupun inovasi pendidikan Islam yang terjadi di era Pandemi Covid-19.Hasil penelitian menjelaskan bahwa pendayagunaan atau inovasi pembelajaran Pendidikan Agama Islam harus segera dilakukan, terutama dalam beberapa metode pembelajaran. Internet sebagai media pembelajaran dapat menjadi alternatif metode pembelajaran pendidikan agama Islam, hal ini bisa dalam bentuk e-learning, atau aplikasi-aplikasi yang memudahkan penyampaian materi pembelajaran, sehingga proses pembelajaran semakin menarik dan tidak membosankan.Kata Kunci: Pembelajaran; Pendidikan Islam; Pandemi Covid-19.